2007
DOI: 10.1021/ja073825i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5-Fluoropyrimidine Nucleotides as Sensitive NMR Probes of RNA Structure

Abstract: Enzymatic synthesis methods for the fluorinated 5'-triphosphate analogues 5F-UTP and 5F-CTP have been developed to facilitate 19F-labeling of RNAs for biophysical studies. HIV-2 TAR RNAs were synthesized using these analogues by in vitro transcription reactions using T7 RNA polymerase. The uniform incorporation of 5F-U or 5F-C analogues into HIV-2 TAR RNA transcripts does not significantly alter the RNA structure or thermodynamic stability. Fluorine observed homonuclear 19F-19F and heteronuclear 19F-1H NOE exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(125 citation statements)
references
References 62 publications
8
117
0
Order By: Relevance
“…We then exploited different chemical shifts of 5-19 F-incorporated pyrimidine nucleotide, in either a single-or doublestranded region of RNA, which has previously been used to probe the secondary structure of RNA (Horowitz et al 1977;Marshall and Smith 1977;Gollnick et al 1986;Chu et al 1992;Kanyo et al 1996;Sahasrabudhe and Gmeiner 1997;Arnold and Fisher 2000;Hammann et al 2001;Olejniczak et al 2002;Hennig et al 2007;Puffer et al 2009) to demonstrate the presence of an alternative conformation of U2-U6 snRNA complex conclusively. The advantage of observing the 19 F nucleus by NMR is the broader range and the greater sensitivity of fluorine chemical shifts in response to the local environment as compared to those of hydrogen because the fluorine nucleus is surrounded by nine electrons vs. a single electron in hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…We then exploited different chemical shifts of 5-19 F-incorporated pyrimidine nucleotide, in either a single-or doublestranded region of RNA, which has previously been used to probe the secondary structure of RNA (Horowitz et al 1977;Marshall and Smith 1977;Gollnick et al 1986;Chu et al 1992;Kanyo et al 1996;Sahasrabudhe and Gmeiner 1997;Arnold and Fisher 2000;Hammann et al 2001;Olejniczak et al 2002;Hennig et al 2007;Puffer et al 2009) to demonstrate the presence of an alternative conformation of U2-U6 snRNA complex conclusively. The advantage of observing the 19 F nucleus by NMR is the broader range and the greater sensitivity of fluorine chemical shifts in response to the local environment as compared to those of hydrogen because the fluorine nucleus is surrounded by nine electrons vs. a single electron in hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have demonstrated that the introduction of 19 F substitutions into the heterocyclic bases is nonperturbing and provides uniquely positioned, sensitive NMR reporter groups to monitor conformational properties of modified RNA (Hennig, Scott, Sperling, Bermel, & Williamson, 2007;Puffer et al, 2009;Scott, Geierstanger, Williamson, & Hennig, 2004). Additional advantages of using spin I ¼ ½ 19 F as an NMR probe are its high sensitivity (83% of the 1 H) combined with 100% natural abundance and a wide chemical shift distribution ($50-fold larger than that of 1 H) (Kitevski-LeBlanc & Prosser, 2012;Rastinejad et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we describe a combination of RNA-labeling techniques as well as NMR methods and applications to a well-established model system, the human immunodeficiency virus (HIV) transactivation response element (TAR) (Fischer et al, 1996;Fischer, Gdaniec, Olejniczak, Bielecki, & Adamiak, 1999;Hennig et al, 2006Hennig et al, , 2007Huang, Varani, & Drobny, 2010; Olejniczak et al, 2002;Olsen et al, 2005;Scott et al, 2004). The Tat (transcription activator)-TAR complex formation provides an essential gene regulatory function for HIV (Marciniak, Calnan, Frankel, & Sharp, 1990;Seelamgari et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of 5-hydroxycytidine (oh 5 C) was carried out using an adapted in vitro enzymatic synthesis method for 5-fluorouridine-5′-triphosphate [31]. The synthesis of oh 5 C began with the C-5-phosphorylation of ribose by ribokinase (rbsK), to give ribose-5-phosphate (R5P) that is further phosphorylated at the C-1 position by 5-phospho-D-ribosyl-α-1-pyrophosphate synthase (prsA) forming 5-phospho-Dribosyl-α-1-pyrophosphate (PRPP).…”
Section: Resultsmentioning
confidence: 99%